2017
DOI: 10.1590/1980-57642016dn11-030009
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in the elderly: A systematic review of pharmacological and non-pharmacological treatments

Abstract: Delirium is a common disorder associated with poor prognosis, especially in the elderly. The impact of different treatment approaches for delirium on morbimortality and long-term welfare is not completely understood.OBJECTIVE:To determine the efficacy of pharmacological and non-pharmacological treatments in elderly patients with delirium.METHODS:This systematic review compared pharmacological and non-pharmacological treatments in patients over 60 years old with delirium. Databases used were: MEDLINE (PubMed), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
2
17
0
2
Order By: Relevance
“…This was in contrast to the decline in cardiovascular mortality observed in the past four decades [ 33 ], as well as the steady drop of approximately 1.5% per year in cancer mortality over the past two decades [ 34 ]. While pursuing an explanation for such a phenomenon, it was found that neither antipsychotic pharmacological therapy [ 35 ] nor non-pharmacological [ 36 ] interventions showed any benefit in terms of decreasing mortality. Greater awareness of delirium over the past three decades would have been expected to result in increasing diagnostic rates and lower mortality simply due to greater detection of milder cases.…”
Section: Discussionmentioning
confidence: 99%
“…This was in contrast to the decline in cardiovascular mortality observed in the past four decades [ 33 ], as well as the steady drop of approximately 1.5% per year in cancer mortality over the past two decades [ 34 ]. While pursuing an explanation for such a phenomenon, it was found that neither antipsychotic pharmacological therapy [ 35 ] nor non-pharmacological [ 36 ] interventions showed any benefit in terms of decreasing mortality. Greater awareness of delirium over the past three decades would have been expected to result in increasing diagnostic rates and lower mortality simply due to greater detection of milder cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with a rapid reduction in brain function and is caused by physical illnesses, usually of systematic involvement. It has a high impact on morbidity and a high risk of lethality ( 43 , 44 ).…”
Section: Approach To the Main Situationmentioning
confidence: 99%
“…However, the diagnosis of delirium and the early identification of its causal factors depend on the training of the health team. After discharge, patients who have developed delirium will need continuous monitoring ( 21 , 43 , 44 ).…”
Section: Approach To the Main Situationmentioning
confidence: 99%
“…3 The disturbance is not due to pre-existing, established, or evolving dementia. The incidence of delirium is 1–2% in the general population, 4 11–29% in hospitalised medical patients, 11–51% in surgical patients, and as high as 82% among patients in intensive care units (ICUs). 5 In elderly patients, the incidence reaches 50% in hospitalised patients.…”
Section: Introductionmentioning
confidence: 99%
“…6 Nevertheless, many cases go undiagnosed. 4 In Dutch nursing homes and residential homes, the prevalence of delirium is 8.9% and 8.2%, respectively, 7 and in a study on lengthy stays in Canadian nursing homes, over the course of 32 months, 40.4% of patients experienced delirium. 8 Nurses’ knowledge about delirium in general and risk factors leading to delirium does not increase with graduation, higher levels of education, or years of nursing practice.…”
Section: Introductionmentioning
confidence: 99%